First insight into extracellular vesicle-miRNA characterization in a sheep in vitro model of inflammation - Ciliberti, Maria Giovanna; Santillo, Antonella; Sevi, Agostino; Albenzio, Marzia; De Leo, Vincenzo; Ingrosso, Chiara; Catucci, Lucia; Caroprese, Mariangela (Frontiers in Veterinary Science, 2023)
Extracellular vesicles (EVs) and their microRNA (miRNA) cargoes have garnered attention in the veterinary field for their regulatory role in various biological processes. This study aimed to (i) evaluate two techniques of EV isolation from sheep peripheral blood mononuclear cell (PBMC) supernatants using the ultracentrifugation (UC) and reagent (REA) methods and (ii) characterize the EV-miRNA profiles after an in vitro inflammatory environment mediated by lipopolysaccharides (LPS). Sheep peripheral blood was collected, and PBMCs were separated using a density gradient reagent. Subsequently, PBMCs were cultured at 37°C for 24 h (5% CO2), and the supernatants were collected to perform the EV isolation. The presence of CD81+ extracellular vesicle marker was determined, and the purity of isolated EVs was calculated as a ratio between the number of isolated EVs and the protein concentration. Moreover, the morphological characterization revealed mainly round-shaped structures with average sizes of 211 nm for EVs isolated by the UC method and 99 nm for EVs isolated by the REA method. Illumina NextSeq sequencing in a single-end mode was used to characterize the miRNA profile, and the differentially expressed (DE) miRNAs were analyzed using a combination of bioinformatics tools. The results revealed that the REA method is reliable for EV isolation from sheep supernatants. It was considered an improvement of the recovery rate and purity of EVs with the enhancement of the number and the expression levels of characterized miRNAs. The EVs isolated by the UC method after an LPS challenge showed 11 DE miRNAs, among which eight miRNAs were upregulated and three were downregulated. On the other hand, the REA method revealed an EV cargo in which eight DE miRNAs were upregulated and 21 DE miRNAs were downregulated. The master miRNA regulators of the biological process were identified by performing the MIRNA-mRNA network analysis, showing that, among the higher representative miRNAs based on the centrality and betweenness, the miR-26a-5p could have a crucial role in the resolution of inflammation. Moreover, the identification of the let-7 miRNA family in all the EVs showed potential targeted genes that regulate the inflammation and immune responses.